Elämän ja entisyyden maisemat : Kolgujev nenetsien arjessa, muistelussa ja kerronnassa - Lukin, Karina (Suomalaisen Kirjallisuuden Seura, 2011)
The dissertation discusses the conceptions of place and landscape amongst Nenets living on the island of Kolguyev or being of Kolguyev descent. The conceptions are examined through the everyday life of the community, oral recollections and narration that unfold meanings related to the island. The research material has been collected in ethnographic fieldwork in 2000 2005. The duration of individual fieldworks varies from two weeks to three months and their total duration is nearly six months. The fieldwork has been conducted both on the island and in the city of Nar yan-Mar. The main methods have been participant observation and recorded and unrecorded informal interviews. In addition to the field work data, archive materials, travel accounts, and other historical texts by outsiders about Kolguyev or the Nenets living in the European side of Russia have been used as a research material. The analysis is based on the idea of the place as a meeting point of the physical features, experiences in them and collective narration about them. The concept sense of place is used to describe the interaction of these three. Lived space manifests individual s or collective sense of place. The places form different kinds of networks of meanings which are called landscapes. Hot spots are places where different meanings accumulate. Furthermore, the material is analysed using the concepts of Tale World and Story Realm by Katherine Young. The Tale World is a realm created during the Story Realm, i.e. the event of narrations. The Tale Worlds are true as such but become evaluated in the Story Realm. The Tale Worlds are seen to arise both from the physical features of a place and from oral tradition, but at the same time these worlds give meanings to the place. The Tale Worlds are one of the central ingredients for the sense of place. One of the most central hot spots in Kolguyev is the arok harbour, where most of the themes of the pre-Soviet Tale Worlds are placed: trade and interaction with the Russians, rituals of the popular ...